Philippine graduate tracer study 4 - Melba V. Tutor; Aniceto C. Orbeta; James Matthew B. Miraflor (Philippine Institute for Development Studies (PIDS), 2019)
A Graduate Tracer Survey (GTS) collects data on the graduate's college experience - skills learned, quality of instruction, and how it relates to employability. GTS allows us to illuminate the relationship between college experience and labor market outcomes, and to formulate course of actions for the higher education sector. In this round, we investigate further and look at the influence of college experience on socio-political participation and life satisfaction. This study reports on the results of the 4th Philippine Graduate Tracer Survey. It covers graduates from AY 2009-2011. A total 11,547 graduates were surveyed, representing 32.7% of the total sample. This GTS round piloted several study design improvements and administrative arrangements aimed at capacitating the CHED. Several challenges affected the response rate, but it is still a successful demonstration of the desired GTS implementation set-up for succeeding rounds. The results show that graduates are motivated by earnings and career advancement in their choice of baccalaureate programs. They are concentrated in a few courses, and except for nursing and IT-related courses, their courses are not the high-paying ones. For graduates of courses without professional license requirement, the median length of working on their first job from graduation is 5 months. It takes 12 months to start on their first job for those who took license-requiring courses. Only 86 out of 100 are economically active.
Keywords: 330; higher education; graduate tracer study